Accumulation of cations in lettuce cultivars under low-cost hydroponic system with brackish waters - Anna C. R. A. da Silva; Gerônimo F. da Silva; Sirleide M. de Menezes; Ruana Í. F. Cruz; José A. Santos Júnior; Mário M. Rolim (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of brackish water to cultivate lettuce can cause nutritional imbalances, impairing production. In this context, the objective of the present study was to evaluate the effect of salinity on the accumulation of dry matter of the aerial part and macronutrients K, Ca and Mg and their relations with Na in lettuce cultivars grown in a low-cost hydroponic system. The experiment was conducted in a randomized block design, in a 6 × 2 factorial scheme, with four replicates. The treatments consisted of six electrical conductivities of the nutrient solution (1.5, 2.5, 3.5, 4.5, 5.5 and 6.5 dS m-1) and two lettuce cultivars, Betty [iceberg] and Mimosa [green-leaf]. Regardless of the evaluated cultivar, the increase in the electrical conductivity of the nutrient solution reduced the accumulation of dry matter in the aerial part. In both cultivars, the increase in the electrical conductivity of the nutrient solution reduced the accumulations of K and Mg and increased Na/K, Na/Ca and Na/Mg ratios. The green-leaf cv. Mimosa showed Ca and Mg accumulations higher than that in the iceberg cv. Betty, regardless of electrical conductivity. The increase in electrical conductivity reduced the accumulation of K, in both cultivars evaluated. The decreasing order in the accumulation of macronutrients and sodium in both cultivars was: K > Na > Ca > Mg.